Recurrent Obstructive Fibrinous Tracheal Pseudomembranes in a Young English Bulldog. (22nd February 2017) - Robin, E.; Guieu, L.V.; Le Boedec, K.
Abstract : Endotracheal intubation is a common procedure, rarely associated with life‐threatening complications (e.g., tracheal rupture, necrosis, foreign body). A 1.5‐year‐old English Bulldog was presented for respiratory distress, with increased respiratory efforts and stridor, 2 days after endotracheal intubation. Cervical and thoracic radiographs disclosed a severe narrowing of the tracheal lumen associated with an intraluminal soft‐tissue structure at the thoracic inlet. Tracheoscopy confirmed the presence of an obstructive fibrinous tracheal pseudomembrane (OFTP) creating a 1‐way valve obstruction. Removal of the OFTP dramatically improved the dog's respiratory function, but the lesion reformed twice despite corticosteroid and antibiotic therapy PO, warranting repeated endoscopic removal of the OFTP. No additional recurrences were observed after treatment with inhaled heparin and N‐acetylcysteine q4h. No respiratory signs were reported 9 months after discharge. Postintubation OFTP has been reported rarely in humans and never described in dogs. Unexplained signs of upper airway obstruction shortly after endotracheal intubation should prompt consideration of OFTP in dogs, even if intubation was uneventful. Unlike its counterpart in humans, OFTP in dogs can reoccur after endoscopic removal, warranting repeated endoscopic extraction. A combination of corticosteroid therapy PO and heparin and N‐acetylcysteine inhalation q4h may be attempted if recurrence is observed.